Morphological analysis of the corneal endothelium in eyes of dogs using specular microscopy - Pigatto,João A.T. (2008)
Both healthy eyes of 10 six-year-old male and female mongrel dogs were studied. With a contact specular microscope the corneal endothelium was examined. Endothelial cells were analyzed in the central and peripheral cornea. Morphological analysis with regard to polymegathism and pleomorphism was performed. Three images of each region with at least 100 cells were obtained. The analysis showed that polygonal cells formed a mosaic-like pattern uniform in size and shape. The predominant number of cells was hexagonal. The polymegathism index was 0.22. The study demonstrates that the morphology of the normal corneal endothelial cells of dogs is similar to that found in the human cornea.